A transnational model of virtual exchange for global citizenship education. (October 2020) - O'Dowd, Robert
Abstract: Virtual exchange is a well-known pedagogical approach in foreign language (FL) education which involves engaging classes in online intercultural collaboration projects with international partners as an integrated part of their educational programmes. This paper begins by reviewing e-tandem and telecollaborative approaches to virtual exchange which are currently being used extensively in FL education and presents two case studies which illustrate the common learning outcomes and limitations of such approaches. I then propose an alternative model of virtual exchange which maintains many of the key characteristics of earlier approaches but which incorporates the principles of global citizenship education and which moves away from bilingual–bicultural approaches. I conclude by outlining the main characteristics of this model and presenting some examples of how this approach could be put into practice.